THE IMPACT OF CREDIT RESTRUCTURING ON BANK HEALTH LEVELS IN MALUKU (CASE STUDY AT PT. BANK MALUKU MALUT) - Purimahua, Sarlotha Y.; Leunupun, Pieter; Tomasila, Mozes; Manufury, Bartha A.; Kesamay, Charolina (International Journal of Social Service and Research, 2024)
Bank Maluku Malut (Malut) is a bank operating in the Malukuku region which also experiences "Non-Performing Loans (NPLs)" problems which can affect the bank's performance and financial health. This study tries to answer the topic of how bank health changes before and after credit restructuring as a form of implementation of OJK policies on the overall health of the bank using a statistical process. The data analysis method applied in measuring the health level of banks is through the use of the "RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital)" method, where the data is analyzed quantitatively descriptively in evaluating the health levels of banks on each factor and its components. The results of the study show that the level of financial health of capital-based banking before and following credit restructuring varies. The level of health of banking is improving in line with credit restructuring. The findings of this study can inform policymakers and financial institutions about the effectiveness of credit restructuring strategies in maintaining bank health and enhancing compliance with regulatory frameworks. It also offers a framework for assessing the implications of similar policies in other banking contexts, potentially guiding future reforms and strategies in the industry.